Fruit fly Bactrocera spp. responses to odour of curry leaves, Murraya koenigii L. Spreng - Widihastuty,; Sri Utami,; Asritanarni Munar,; Desi Ardilla,; Khairunnisa Rangkuti, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bactrocera spp. fruit fly is a major pest for various horticultural crops, particularly fruit trees. The intensity of fruit fly attacks in several Indonesia areas shows a fairly large variation and it needs an intensive control program. Moreover, this research was conducted to determine the semiochemical compounds of curry leaves for controlling fruit flies. The results showed that the volatile compounds of curry leaves from the GC-MS analysis were dominated by compounds of the terpene group, namely caryophyllene compounds (36.9%), hexadecene compounds (22.72%) and α-selinene compounds (20.43%). Therefore, the results of the odor detection test carried out on the Y-tube olfactometer showed that male fruit flies were more attracted to the aroma of curry leaves around 80% than female fruit flies around 57.5%. The results of this research can be developed as attractant of male fruit flies and trap them so that later it is expected to reduce fruit fly pest populations.